MANAGEMENT OF REPEAT BREEDING UNDER FIELD CONDITIONS USING HORMONAL AND NON-HORMONAL DRUGS IN COWS - KUMAR, RAJESH; DHAMI, A J; BUTANI, M G; KAVANI, F S; SARVAIYA, N P; KILLEDAR, ANKITA (The Indian Journal of Animal Reproduction, 2023)
A study was carried out on 4 7 repeat breeding crossbred cows to evaluate the therapeutic efflcacy of various hormonal and non-hormonal drugs in improving their reproductive efficiency. 19, 11 and 9 cows were treated with 0.02 mg GnRH (Receptal 5 ml i/m), just after Al, 500 mg of hydroxy-progesterone cap oate (Duraprogen 2 ml i/m)’on day 4 post-Al, and antibiotics ceftriaxone (lnj. Velacef 2 gm) or cephalexin (Lixen 4 gm) i/ut 12-24 hrs post-Al, respectively. The overall conception rate was 73.68, I.· 8’1 .82 and 77.77 %, respectively, (P<0.05). The conception rate in the treatment cycle itself for the three group’s was 52.63, 27.27 and 22.22 %; respectively. Maximum cows conceived in the treatment cycle itself indicating beneficial effect of GnRH In inducing fertile estrus and CL growth. Progesterone and antibiotics treatment also significantly Improved conception rate and reduced fertile estrus interval. Hence, all three regimes and hormones in particular are recommended for their judicious use in the field to solve the problem of repeat breeding in crossbred cows.